2017
DOI: 10.1016/j.jphys.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ beliefs and attitudes influence clinical practice in chronic low back pain: a systematic review of quantitative and qualitative studies

Abstract: Both quantitative and qualitative studies showed a relationship between treatment orientation and clinical practice. The inclusion of qualitative studies captured the influence of patient factors in clinical practice in chronic low back pain. There is a need to recognise that both beliefs and attitudes regarding treatment orientation of physiotherapists, and therapist-patient factors need to be considered when introducing new clinical practice models, so that the adoption of new clinical practice is maximised.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 48 publications
4
124
1
7
Order By: Relevance
“…The facilitation of a self‐management approach was achieved by giving specific advice and exercise to reduce patients’ pain levels, manage their flare‐ups and give them confidence to be more active. Support and advice from healthcare professionals to continue to exercise during short exacerbations of pain may be crucial to reduce fear avoidance and inactivity, and positively affect patients' attitudes, beliefs and health outcomes (Darlow et al, ; Gardner et al, ; Littlewood, Mawson, May, & Walters, ). Reducing physical inactivity is essential as it is one of the 10 leading risk factors for death worldwide, costing an estimated €1.9 billion a year in healthcare and €9.4 billion a year in economic costs in the UK (World Health Organization, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facilitation of a self‐management approach was achieved by giving specific advice and exercise to reduce patients’ pain levels, manage their flare‐ups and give them confidence to be more active. Support and advice from healthcare professionals to continue to exercise during short exacerbations of pain may be crucial to reduce fear avoidance and inactivity, and positively affect patients' attitudes, beliefs and health outcomes (Darlow et al, ; Gardner et al, ; Littlewood, Mawson, May, & Walters, ). Reducing physical inactivity is essential as it is one of the 10 leading risk factors for death worldwide, costing an estimated €1.9 billion a year in healthcare and €9.4 billion a year in economic costs in the UK (World Health Organization, ).…”
Section: Discussionmentioning
confidence: 99%
“…Support and advice from healthcare professionals to continue to exercise during short exacerbations of pain may be crucial to reduce fear avoidance and inactivity, and positively affect patients' attitudes, beliefs and health outcomes (Darlow et al, 2012;Gardner et al, 2017;Littlewood, Mawson, May, & Walters, 2015). Reducing physical inactivity is essential as it is one of the 10 leading risk factors for death worldwide, costing an estimated €1.9 billion a year in healthcare and The physiotherapists in the present study suggested that the adaptability of Pilates for a range of musculoskeletal conditions was achieved by using a combination of exercises for the trunk, and upper and lower limbs, aligned to participants' function, to restore stability deficits and improve global strength (Brooks, Kennedy, & Marshall, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions from previous qualitative research have been inconsistent in this regard. Some studies suggest that physiotherapists lack a solid understanding of biopsychosocial factors and associated effects on patient presentation (Gardner et al, 2017;Singla, Jones, Edwards, & Kumar, 2015;Synnott et al, 2015) and that practice is still entrenched in a biomedical approach (Barlow & Stevens, 2014;Mudge, Stretton, & Kayes, 2014). Alternative research concluded that physiotherapists appreciate the importance of addressing biopsychosocial factors that may impede rehabilitation and, however, found such issues challenging to manage (Sanders, Foster, Bishop, & Ong, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome for this systematic review will be students'/clinicians' attitudes and beliefs regarding people with chronic pain. Evidence shows that attitudes and beliefs directly influence clinicians' behaviour with patients (Gardner, 2017).…”
Section: Primary Outcomesmentioning
confidence: 99%